Uplift and denudation history of the eastern Dead Sea rift flank, SW Jordan: Evidence from apatite fission track thermochronometry. Issue 5 (18th October 2013) - Feinstein, S.; Eyal, M.; Kohn, B. P.; Steckler, M. S.; Ibrahim, K. M.; Moh'd, B. K.; Tian, Y.
Abstract [1] The Dead Sea rift (DSR), developed along the Dead Sea transform plate boundary, is characterized by salient flanks and morphotectonic asymmetry. Apatite fission track thermochronology (AFT) along 1200 m high vertical profiles in Neoproterozoic basement and overlying Cambrian sandstone in southwestern Jordan is used to reconstruct timing, magnitude, and rate of uplift and denudation of the eastern DSR flank and examine its relationship to rift development and its flank landscape. Time‐temperature models based on AFT data suggest three major Phanerozoic heating and cooling episodes, Late Paleozoic, Early Cretaceous, and Oligocene. The latest episode, on which this study focuses, indicates uplift of 3.8±0.3 km under a moderate paleogeothermal gradient. About 40% of the uplift was tectonically driven with the remainder attributed to isostatic rebound in response to denudation and erosion. Models suggest that uplift commenced in the Oligocene with a considerable part occurring prior to development of the DSR, despite being 200 km from the Red Sea‐Gulf of Suez rift margin. Uplift is probably part of a regional rearrangement along the western Arabian platform margin occurring at the time of Red Sea rift initiation. Transition from primarily sedimentary layer stripping, most likely by scarp retreat, to one of dominantly incision of the underlying crystalline basement occurred in Late Miocene‐Pliocene time following enhanced subsidence and development of a low base level in the DSR. Consequently, the magnitude of uplift by isostatic rebound due to incision exceeded lowering by surface truncation and increased summit elevation and riftward flexing of the flank.